PROBLEMATIZING ENVIRONMENTAL JUSTICE IN ANKUR BISEN’S WASTED: THE MESSY STORY OF SANITATION IN INDIA, A MANIFESTO FOR CHANGE WITH INSIGHTS FROM THE INDIGENOUS PHILOSOPHY OF LIFE - Alex, Minu; Lakshmi, S. Geetha (ShodhKosh: Journal of Visual and Performing Arts, 2022)
A conversation about environmental justice uncovers the intricate relationship between the environment and the concept of 'justice'. In Ankur Bisen's work titled "Wasted: The Messy Story of Sanitation in India, A Manifesto for Change," he delves into the complexities of waste management within India's socio-political landscape. Bisen highlights how societal biases based on caste have significantly influenced sanitation practices, hindering the acceptance of ecological awareness as a communal obligation. The text further examines the power dynamics that contribute to the system's apathy towards individuals living in unsanitary conditions. It critiques both societal indifference and the audacity of the system, exploring the subtle workings of power politics that shape social perspectives, and drawing insights from Foucault's theories on power structures. The paper also delves into the ways indigenous cultures actively safeguard the environment, showcasing a profound sensitivity often absent in today's consumer-driven, modern society. Tribal traditions brim with a deeply ingrained eco-consciousness, offering invaluable lessons on integrating ecological practices into everyday life. This comparison between an eco-sensitive culture and our current world, steeped in excess and waste, holds immense significance as a guiding philosophy—one that suggests a shift towards a more adaptive global ethos.